From curriculum to syllabus design: The different stages to design a programme - Nunan barlet (Al-Qanṭara, 2022)
Abstract Designing your own programme as an in-service teacher might be really time consuming and also difficult to teach how to do it to pre-service teachers. But in the long run it might be rewarding when knowing that we are giving the students what they want and need and not just what has been decided by the authorities. In this paper the following will be considered: What is curriculum, course and syllabus and possible approaches to course design? What is meant by articulating your beliefs? What is defining the context? What are goals, objectives and needs analysis? What stages are followed in designing a course? Curriculum includes the philosophy, purposes, design and implementation of a whole programme. A course according to Hutchinson and Waters (1996) is an integrated series of teaching learning experiences, whose ultimate aim is to lead the learners to a particular state of knowledge. And syllabus is the specification and ordering of content of a course or courses. When reflecting on our own teaching we know that most of the time, we have used a commercial textbook as our syllabus for the different levels of English we have taught along our in-service years. Sometimes we modify something or add what we consider is missing in the current book used. But we do not take into consideration that most of the books have not been designed specifically for our different contexts. It is not the same to teach to students from a capital city than it is to teach students in a Secondary School up in the mountains where they do not have any kind of access to computers and less to the internet.